The Relationship Between Nutritional Status and Chemotherapy Toxicity in Patients with Cervical Cancer: A Systematic Review - Bangar Parlinggoman Tua; Yahya Nurlianto; Mutia Juliana (The International Journal of Medical Science and Health Research, 2025)
Introduction: Cervical cancer imposes a significant global health burden, disproportionately affecting low- and middle-income countries where malnutrition is also endemic. Antineoplastic therapy, particularly concurrent chemoradiotherapy (CCRT) with platinum-based agents, is the standard of care but is associated with severe toxicities. This systematic review investigates the central hypothesis that poor nutritional status—defined by a range of anthropometric, serological, and body composition metrics—is an independent and significant predictor of increased chemotherapy-related toxicity in cervical cancer patients. Methods: This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. A systematic search of PubMed, Scopus, and the Cochrane Library was performed to identify studies evaluating the relationship between nutritional status and chemotherapy toxicity in cervical cancer patients. Eligibility criteria were based on the Population (cervical cancer patients), Exposure (malnutrition), Comparison (well-nourished), and Outcome (toxicity) framework. Methodological quality was appraised using the Cochrane Risk-of-Bias 2 (RoB 2) tool for randomized controlled trials (RCTs) and the Newcastle-Ottawa Scale (NOS) for observational studies. Results: A total of 16 studies (2 RCTs and 14 observational cohorts) met the inclusion criteria. The results demonstrate a consistent and statistically significant association between malnutrition and increased treatment toxicity. Specifically, poor nutritional status assessed by the Patient-Generated Subjective Global Assessment (PG-SGA) was an independent predictor of both Grade 3+ toxicity and Toxicity-Induced Modification of Treatment (TIMT). Sarcopenia (low Skeletal Muscle Index, SMI) was significantly associated with higher rates of treatment interruption due to toxicity (p=0.024) and was a determining factor for Grade 3+ adverse events. Low Body Mass Index (BMI < 18.5 kg/m²) was linked to severe Grade 3/4 gastrointestinal complications, including bowel obstruction (p<0.001). A low Prognostic Nutritional Index (PNI) correlated with increased severity of fatigue, nausea, and diarrhea (p<0.05). Nutritional interventions, such as omega-3 supplementation, were shown in an RCT to significantly reduce the incidence of chemotherapy toxicity. Discussion: The evidence converges to confirm that malnutrition is a critical determinant of chemotherapy tolerance. The mechanisms are multifactorial. Pharmacokinetic alterations, such as hypoalbuminemia, increase the free, active fraction of protein-bound drugs, leading to toxicity. Pharmacodynamic failures, particularly in sarcopenic patients, result in a relative overdose from standard Body Surface Area (BSA)-based dosing due to a smaller volume of distribution. Malnutrition also impairs the host's ability to repair healthy tissue (e.g., gut mucosa, bone marrow) damaged by chemotherapy. Conclusion: Nutritional status is a powerful, modifiable predictor of severe chemotherapy-related toxicity in cervical cancer patients. These findings mandate the integration of nutritional screening (e.g., PG-SGA) and objective assessment (e.g., CT-based SMI) into routine oncological practice. Such screening can risk-stratify patients and trigger pre-emptive nutritional interventions to improve treatment tolerance, reduce toxicity-related interruptions, and optimize clinical outcomes